First occurrence of a mawsoniid (Sarcopterygii: Actinistia), Mawsonia soba sp. nov., in pre-Aptian Cretaceous deposits from Cameroon. (June 2018) - Brito, Paulo M.; Cupello, Camila; Yabumoto, Yoshitaka; Hell, Joseph V.; Brunet, Michel; Otero, Olga
Abstract: Coelacanth remains from the Lower Cretaceous (pre-Aptian) freshwater deposits of the Babouri Figuil Basin, Northern Cameroon are described as a new taxon Mawsonia soba sp. nov. based on two characters: four openings in the dentary for the branch of the trigeminal nerves and an extremely rugose and disorganized ornamentation of the bones. M. soba sp. nov. known by some three-dimensionally partially preserved specimens represents the first actinistian described from Cameroon. This discovery attests the presence of Mawsonia in the African counterpart of the continental pre-rift and rift environments where only Brazilian members were known so far. The fact that the Cameroonian coelacanth belongs to a new species suggest a certain endemism at least in this African basin. Highlights: Mawsoniid remains from the pre-Aptian of Cameroon are described for the first time. These remains are identified as a new taxon. This register expanding the geographical range of Mawsonia .